PG127 Medical student 'on-call bleep-a-thon'. (10th November 2020) - Cathie, Victoria; Williams, Matt; Toft, Lisa; Williams, Emma
Abstract : Introduction: Portsmouth Hospitals University NHS (PHU) welcomes undergraduate medical students from local University providers and aims to provide broad, curriculum based teaching. The PHU Simulation Centre Simulation Fellowship provided a unique opportunity to deliver novel ward based in situ simulation training. A bleep-holder session with case teaching was devised to teach prioritisation and on-call task management in response to student enquiries to the practical life of a junior doctor. It was to be immersive training within the natural chaos of the ward, with the stress and benefit of a true MDT. Method/Project Description: The aim was to provide realistic, practical preparation for junior doctor out of hours responsibilities. The objective was to simulate a 2hour evening on-call shift, with each student attending multiple jobs across many wards. Thus offering an opportunity to consider prioritisation of clinical care and managing expectations of colleagues within a realistic and safe environment. Starting with a 18:00pm pre-brief, students were allocated a bleep and subsequently contacted to attend a simulation station 'job'. Each student would visit between 4–7 stations each individually, with facilitated training lasting approximately 10minutes. Themes included acute or deteriorating patient, post falls management and confirmation of death. During each station, the student would be contacted with further 'jobs' by the simulation coordinator posing as a nurse, including non-urgent reviews and prescriptions. The student was expected to prioritise tasks, demonstrate case load management and effective communication before attending the next 'job'. Station facilitators provided feedback and contributed to the post training debrief at 20:00pm. Each student completed a free text questionnaire discussing knowledge improvement and their experience post simulation training. Its validity was assed using a 1–5 confidence improvement rating scale for each station scenario. Outcome: 3 'Bleep Holder' training sessions involved 22 students. Confidence scales demonstrated global improvement across all scenarios, with verbatim including the request for further educational opportunities: 'the experience of receiving multiple bleeps was confusing but an important lesson' 'I learnt how to confirm death + practised handover, it was very useful' 'I really enjoyed it and would go as far as to say it is the most enjoyable teaching I've had in medical school so far!' Challenges highlighted from these sessions included faculty availability, room space or availability and pitching teaching at the correct level. Learning from the delivery of these sessions has successively shaped future training. Discussion/Conclusions/Recommendations: Following the initial success, bleep holder teaching has continued to evolve and has since been delivered to 23 new students. Future developments include participants being followed up within their first year of working to explore the usefulness of the training and examine where participants are able to demonstrate application of learning into clinical practice.